Raaz: A Transdisciplinary Exploration at the Intersection of Bioart, HCI, and Community Engagement - Stamato, Lydia; Higgins, Erin; Prottoy, Hasan Mahmud; Asgarali-Hoffman, S. Nisa; Scheifele, Lisa; Dusman, Linda; deCarvalho, Tagide; Ascencao, Teresa; Hamidi, Foad (Frontiers in Computer Science, 2022)
Living organisms and their biological properties, including capacity for transformation and representation of information, offer exciting and inspiring opportunities for transdisciplinary art and design explorations. While an emerging body of work is increasingly investigating the possibilities at the intersection of interactive computing, biology, and art, more work is needed to investigate the potential of these approaches for supporting community and public engagement and participation in art, science, and technology. In this project, we describe a multimedia transdisciplinary bioart installation and hands-on agar art activity that we presented to members of the public in a community biology lab setting. Using short interview, observations, and questionaries, we investigated attendees’ reactions and impressions of the experience and found that the event generated transdisciplinary reflections, invited participants to bear on their previous knowledge and experience to engage with different aspects of the work, and benefitted from contextualization by artists.